Certification, forest conservation, and cattle: theories and evidence of change in Brazil - Newton, Peter; Alves Pinto, H.N.; Guedes Pinto, L.F. (Wiley, 2015)
Voluntary certification programs for agricultural and forest products have beendeveloped to improve the environmental and social sustainability of produc-tion processes. The new Sustainable Agriculture Network (SAN) cattle certifi-cation program aims to reduce deforestation in the cattle supply chain, witha focus on Brazil. Drawing on information from interviews with key actors inBrazil, this article discusses the mechanisms that may enable the SAN cattleprogram to achieve these goals and to avoid critiques that have been leveled atother commodity certification programs. The program sets higher standards forsustainability than any existing policy or incentive mechanism. Participationin the program may generate significant indirect financial and non-financialbenefits. The program may also influence the supply chain more widely: bydemonstrating that certifiable, traceable, sustainable cattle production is vi-able; by “raising the bar” of sustainability standards through rigorous criteria;and by creating new markets and incentives. While the scaling up and impactof the SAN cattle program will depend in part on how it is supported or con-strained by other interventions in the same sector, the program appears to becharacterized by a rigorous program design that is necessary, if not sufficient,to catalyze reduced rates of forest loss